2001
DOI: 10.1097/00005768-200110000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent cardiovascular and resistance training in healthy older adults

Abstract: Concurrent CVT and RT is as effective in eliciting improvements in cardiovascular fitness and 5RM performance as CVT or RT, respectively. Moreover, incorporating both CVT and RT in exercise programs for older adults may be more effective in optimizing aspects of functional fitness than programs that involve only one component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
117
0
34

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(170 citation statements)
references
References 26 publications
19
117
0
34
Order By: Relevance
“…Wood et al 9 reported reduction in HR, with no alteration Table 1. Physical characteristics of the participants of the resistance training group (TG and control group CG) at the pre and post eight weeks of experimental period moments (values in mean ± standard deviation).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wood et al 9 reported reduction in HR, with no alteration Table 1. Physical characteristics of the participants of the resistance training group (TG and control group CG) at the pre and post eight weeks of experimental period moments (values in mean ± standard deviation).…”
Section: Discussionmentioning
confidence: 98%
“…However, the chronic effect of resistance training (RT) in the cardiovascular function of the elderly remains controversial. In normotensive elderly subjects, some studies have not verified any significant alteration in systolic blood pressure (SBP) and diastolic blood pressure (DBP) at rest after performance of RT 9 . On the other hand, different studies have shown isolated reduction in SBP 10 , DBP 11 or in both simultaneously 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Já para o músculo reto femoral o grupo TC não apresentou melhora significativa ao se comparar antes e após a aplicação do programa de treinamento. Na avaliação da área de secção transversal do músculo vasto lateral os achados neste estudo são consistentes com a pesquisa de Izquierdo et al 25 e Wood et al 26 , os quais relataram que em idosos o treinamento combinado foi tão eficaz no condicionamento cardiovascular e na força quanto o treinamento somente de força e aeróbico realizado duas vezes na semana.…”
Section: Tf (N=10)unclassified
“…Foram encontradas 12 referências sobre o treinamento com pesos em longo prazo e a PA de repouso em normotensos (7,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) e seis referências em hipertensos (5,32,(40)(41)(42)(43) . Dos estudos com normotensos, duas referências possuíam dois grupos experimentais (35,37) .…”
Section: Treinamento Com Pesos E Pressão Arterial De Repousounclassified
“…Dessa forma, envolvendo normotensos, foram considerados 14 grupos de treinamento. Desses grupos envolvendo normotensos, 11 reportaram aumento significativo da força muscular (7,29,30,32,(34)(35)(36)(37)39) ; cinco, redução na PAS (7,31,35,37) ; quatro, redução na PAD (7,31,35) . Os quatro que reportaram redução na PAD também relataram redução na PAS.…”
Section: Treinamento Com Pesos E Pressão Arterial De Repousounclassified